PENGARUH AUDIT TENURE, INDEPENDENSI, KOMPETENSI, UKURAN KAP, DAN FEE AUDIT TERHADAP KUALITAS AUDIT - CHUSNUL CHOTIMAH, ANNISA (Jurnal Akuntansi AKUNESA, 2017)
This research aims to test the influence of tenure, audit independence, competence, the size of the public accounting and auditing of the quality audit fee on existing public accountant in Surabaya.This research uses questionnaire which distributed to 20 public accountant in Surabaya, based on convenience sampling method. Using analysis of multiple linear regression, the results showed that tenure, independence and audit fee significantly affect audit quality. However, competencies and size of the public accountant have no significant influence on audit quality.    Keywords: Audit Quality, Audit Tenure, Independence, Competence, Size of The Public Accountant, Audit Fee.